Identification of heavy work investment antecedents: a research on digital leadership - Turan-Torun, Burcu; Oktaysoy, Onur; Kobanoglu, Mehmet Selman; Topcuoglu, Ethem; Yenikaya, Muhammed Akif; Topcuoglu, Vurgun; Uygungil-Erdogan, Selen (Frontiers in Psychology, 2025)
IntroductionIn today’s world, which is referred to as the era of digital transformation, the expectations from the leader role are changing significantly and digital leadership understanding draws attention as a reflection of these expectations. This study examines the impact of digital leadership on employees’ job performance, job satisfaction and career satisfaction and examines the mediating role of Heavy Work Investment (HWI) in this relationship. Within the framework of the sub-dimensions of HWI such as Time Commitment (TC) and Work Intensity (WI), the study investigates how employees’ investment in their work is shaped and the guiding role of digital leaders in this process.MethodsThis study, which aims to determine the mediating role of HWI in the effect of digital leadership on job performance, job satisfaction and career satisfaction of employees, was conducted with 393 employees working in SMEs operating in the IT sector. The data obtained by convenience sampling methods were analyzed with Smart-PLS program. The study was shaped on the axis of structural equation modeling.ResultsThe findings of the analysis reveal that digital leadership has a significant effect on employees’ job performance, job satisfaction and career satisfaction. In addition, it has been determined that HWI creates different mediation mechanisms in terms of its sub-dimensions TC and WI in the relationship between digital leadership and employees’ job performance, job satisfaction and career satisfaction.DiscussionThe research findings reveal that digital leadership has positive effects on employees’ job performance, job satisfaction and career satisfaction and that HWI plays a partial mediating role in this process. It is noteworthy that while WI is found to be a strengthening factor in this relationship, the effect of TC on job satisfaction and career satisfaction is not significant. This suggests that TC may lead to negative consequences such as burnout and stress instead of increasing employees’ motivation and performance. Moreover, practices that increase employee engagement in the digital transformation process appear to play a critical role in maintaining organizational efficiency and employee well-being in the long run. While the findings are in line with the existing literature, they suggest that a deeper understanding of the interaction dynamics between digital leadership and HWI is needed.